The Therapeutic Effects of Curcumin on Oral Disease: A Systematic Review - Indriyani N; Nur'aeny N (Clinical Pharmacology: Advances and Applications)
Novi Indriyani,1 Nanan Nur’aeny2 1Oral Medicine Residency, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia; 2Oral Medicine Residency Program, Department of Oral Medicine, Faculty of Dentistry, Padjadjaran University, Bandung, IndonesiaCorrespondence: Novi Indriyani, Oral Medicine Residency Program, Department of Oral Medicine, Faculty of Dentistry, Padjadjaran University, Jalan Sekeloa Selatan I, Bandung, West Java, 40132, Indonesia, Tel +62 8971557962, Fax +62 22 7794121, Email novi23002@mail.unpad.ac.idIntroduction: Curcumin is an extract from herbal plants that has been implicated in the treatment of any disease, including oral disease. There are various types of curcumin formulation as the option of the therapy. The aim of this review is to describe the curcumin mechanism in reducing the severity, pain score, and oral lesion size as the therapeutic effects.Methods: This systematic review used the Preferred Reporting Items for Systematic Review and Meta Analysis (PRISMA) guidelines. Databases used for articles include PubMed, Science Direct, and Scopus with inclusion criteria published from 2014 to 2024, full text, in English, and randomized controlled trial (RCT).Results: The present study included 21 RCTs with a total of 1244 individuals. In this study, curcumin was most commonly used for oral submucous fibrosis, with 9 studies demonstrating that curcumin has anti-inflammatory properties and inhibits collagenase. All studies demonstrate that curcumin produces significant results in the management of oral disease. The remain studies showed curcumin has antioxidant, inhibit collagenase, antifungal, and wound healing properties for oral leukoplakia, recurrent aphthous stomatitis (RAS), oral lichen planus (OLP), and denture stomatitis.Conclusion: Curcumin has anti inflammatory, antioxidant, inhibit collagenase, antifungal, and wound healing properties for reducing the severity of lesion, pain score and oral lesion size as the therapeutic effects in the patients with oral disease including OSMF, mucositis, leukoplakia, RAS, OLP, and denture stomatitis.Keywords: curcumin, oral disease, therapeutic effect